NEOSCOPE: A randomised phase II study of induction chemotherapy followed by oxaliplatin/capecitabine or carboplatin/paclitaxel based pre-operative chemoradiation for resectable oesophageal adenocarcinoma. (March 2017) - Mukherjee, Somnath; Hurt, Christopher Nicholas; Gwynne, Sarah; Sebag-Montefiore, David; Radhakrishna, Ganesh; Gollins, Simon; Hawkins, Maria; Grabsch, Heike I.; Jones, Gareth; Falk, Stephen; Sharma, Ricky; Bateman, Andrew; et al.
Abstract: Background: Oxaliplatin-capecitabine (OxCap) and carboplatin-paclitaxel (CarPac) based neo-adjuvant chemoradiotherapy (nCRT) have shown promising activity in localised, resectable oesophageal cancer. Patients and methods: A non-blinded, randomised (1:1 via a centralised computer system), 'pick a winner' phase II trial. Patients with resectable oesophageal adenocarcinoma ≥ cT3 and/or ≥ cN1 were randomised to OxCapRT (oxaliplatin 85 mg/m 2  day 1, 15, 29; capecitabine 625 mg/m 2 bd on days of radiotherapy) or CarPacRT (carboplatin AUC2; paclitaxel 50 mg/m 2  day 1, 8, 15, 22, 29). Radiotherapy dose was 45 Gy/25 fractions/5 weeks. Both arms received induction OxCap chemotherapy (2 × 3 week cycles of oxaliplatin 130 mg/m 2  day 1, capecitabine 625 mg/m 2 bd days 1–21). Surgery was performed 6–8 weeks after nCRT. Primary end-point was pathological complete response (pCR). Secondary end-points included toxicity, surgical morbidity/mortality, resection rate and overall survival. Statistics: Based on pCR ≤ 15% not warranting future investigation, but pCR ≥ 35% would, 76 patients (38/arm) gave 90% power (one-sided alpha 10%), implying that arm(s) having ≥10 pCR out of first 38 patients could be considered for phase III trials. ClinicalTrials.gov:NCT01843829 . Funder: Cancer Research UK (C44694/A14614). Results: Eighty five patients were randomised between October 2013 and February 2015 from 17 UK centres. Three of 85 (3.5%) died during induction chemotherapy. Seventy-seven patients (OxCapRT = 36; CarPacRT = 41) underwent surgery. The 30-d post-operative mortality was 2/77 (2.6%). Grade III/IV toxicity was comparable between arms, although neutropenia was higher in the CarPacRT arm (21.4% versus 2.6%, p = 0.01). Twelve of 41 (29.3%) (10 of first 38 patients) and 4/36 (11.1%) achieved pCR in the CarPacRT and OxcapRT arms, respectively. Corresponding R0 resection rates were 33/41 (80.5%) and 26/36 (72.2%), respectively. Conclusion: Both regimens were well tolerated. Only CarPacRT passed the predefined pCR criteria for further investigation. Highlights: Oxaliplatin-capecitabine (OxCap) and carboplatin-paclitaxel (CarPac) based neo-adjuvant chemoradiotherapy (nCRT) have shown promising activity in localised, resectable oesophageal cancer. A randomised phase II 'pick a winner' trial was conducted to assess which regimen to take forward to a phase III trial. Both regimens were well tolerated. Only CarPacRT passed the predefined pathological complete response (pCR) criteria for further investigation.